Custody visiting: The watchdog that didn’t bark - Kendall, John (Criminology & criminal justice, 2022)
This article argues that in qualitative research into the work of a regulator, it is as important to watch out for that regulator’s omissions and silences as it is to examine what the regulator does and says. The argument is illustrated by data drawn from a study of the Independent Custody Visiting Scheme, the purpose of which is (or should be) to safeguard detainees and to deter police from misconduct which might lead to deaths in custody. Research into the scheme included using the technique of watching out for what the visitors did not do and did not say. The data obtained by this method are interpreted through the lens of Lukes’ theory of power to suggest that this watchdog has been debarked as a result of the power of the police.